The Dragon Den - Murray, William; Stories by Jill Corby; Illustrated by Chris Russell (London Ladybird)
An easy reader, which is part of a series intended to cover the three main methods of teaching reading. Its publication coincides with the launch of the new phonic scheme "Say the Sounds" and has a simplified message to parents.
Include Color Illustrations
Key Words Reading Scheme
Keywords: Play